Association between occupational balance and the physical and mental health of the university community: an observational study - Huertas-Hoyas, Elisabet; García-Bravo, Cristina; Pérez-Corrales, Jorge; Bullón-Benito, Elisa; Fernández-Gómez, Gemma; Rodríguez-Pérez, Mª Pilar (Frontiers in Public Health, 2025)
AimsThe study aims to explore the influence of occupational balance on the physical and mental health of working university students and to describe the existing correlations within the university community between sociodemographic variables and physical and mental health.Materials and methodsThis is a descriptive cross-sectional study. Participants were recruited through a convenience sampling strategy, targeting students enrolled at the university who met the inclusion criteria and voluntarily agreed to participate. The assessment instruments used were: Occupational Balance Questionnaire, Spanish version (OBQ-E), Depression, Anxiety and Stress Scale 21 (DASS-21), and the Spanish version of the International Physical Activity Questionnaire Short Form (IPAQ-SF).ResultsA sample of 89 participants was obtained, with a mean age of 25.42 ± 8.33. Significant differences were observed in sociodemographic and emotional variables between working and non-working students. The results indicate that non-working students have higher levels of anxiety (t = 2.7, p < 0.01), while working students show lower levels of occupational balance (t = 0.195, p < 0.05) and prefer light physical activities over moderate ones. Additionally, significant negative correlations were found between age and anxiety (r = −0.440, p < 0.0001), depression (r = −0.238; p < 0.05), stress (r = −0.399, p < 0.001) and vigorous activity (r = −0.223, p < 0.05), as well as between occupational balance and anxiety (r = −0.334, p < 0.0001), depression (r = −0.443, p < 0.0001), and, vigorous activity (r = +0.283, p < 0.001) stress (r = −0.531, p < 0.0001) variables.ConclusionOccupational balance has a significant impact on the physical and mental health of working university students. Those with better occupational balance show lower levels of depression, anxiety, and stress. Further studies with larger samples are needed to corroborate these findings.